Mapping scientific knowledge and future directions on exercise and depression: A bibliometric study - Mohammad Hendra Setia Lesmana; Rathi Paramastri; Muhammad Solihuddin Muhtar; Vivi Leona Amelia; Dina Nur Anggraini Ningrum; Herry Susanto; Isna Hudaya; Min-Huey Chung; Muhammad Muslih; Ade Sutrimo (Physical Therapy Journal of Indonesia, 2026)
Background: Exercise is widely recognized as a supplementary or alternative treatment for depression, yet comprehensive scientific mapping in this area remains limited. This study aimed to explore the current research landscape, key findings, and future trends related to exercise and depression across all age groups. Methods: We used the Web of Science database to collect articles on exercise and depression from 2002 to 2022. Eligible data were extracted and analyzed using R Studio with the Bibliometrix package to generate descriptive summaries, annual trends, country and institution outputs, journal impact, and research hotspots. Results: The majority of publications on the subject of exercise and depression originate from the United States and China, with 258 and 161 publications, respectively. Notably, Chongqing Medical University and Harvard University stand out as leading institutions in this field, each contributing 48 publications. The Journal of Affective Disorders, recognized for its high impact and Q1 status, serves as a foundational resource in the exploration of exercise and depression. The thematic map and topic trend analysis highlight aerobic exercise and tai chi as promising exercises, potentially targeting the hippocampus and BDNF in the context of depression. Furthermore, it is noteworthy that PHQ-9 and HADS are frequently utilized measurements in ongoing research endeavors. Conclusion: This study provides a summary of the field about exercise and depression, highlighting emerging trends, sources, prominent institutions, and key topics using bibliometric analysis and network visualization. Our findings offer valuable insights that can guide future research directions and inform clinical practice.